Incident Kaposi sarcoma during the expansion of antiretroviral therapy eligibility in Nigeria: a retrospective cohort study - Maxwell. O. Akanbi; Lucy. A. Bilaver; Chad Achenbach; Lisa. R. Hirschhorn; Adovich. S. Rivera; Orimisan. S. Adekolujo; Kehinde. U. A. Adekola; Olugbenga. A. Silas; Patricia. A. Agaba; Oche Agbaji; Nathan. Y. Shehu; Solomon. A. Sagay; et al. (BMC Cancer, 2023)
Abstract Introduction The expansion of antiretroviral therapy (ART) eligibility could lead to earlier initiation of Human Immunodeficiency Virus (HIV) treatment and consequently reduce the risk of HIV-associated Kaposi Sarcoma (KS). We investigated the impact of changes in the Nigerian HIV treatment guidelines on KS incidence among adults enrolled in HIV care in Nigeria. Methods We analyzed data of adults who enrolled for HIV care from January 2006 to December 2016 at one of Nigeria’s largest HIV treatment centers. Based on changes in HIV treatment guidelines, we classified 2006–2009 as the pre-expansion period and 2010–2016 as the post-expansion period. We used Kaplan Meier curves to compare the incidence of KS in the pre-expansion to the post-expansion period. We used Cox regression models to assess the hazard for incident KS between the two periods after adjusting for potential confounders. Results Among 14,479 patients with HIV, the overall KS incidence was 2.35; 95% CI 2.01–2.74/1,000 person-years. The incidence of KS decreased from 2.53 to 1.58 per 1,000 person-years from 2006 to 2009 to 2010–2016. In models adjusting for age, sex, CD4-T cell count, and ART use, the risk for KS remained lower in 2010–2016 compared to 2006–2009. In analyses restricted to time on ART, there was no significant difference in KS incidence between HIV patients who enrolled in 2006–2009 and 2010–2016 after adjusting for age, sex, and CD4 T-cell count. Conclusion The expansion of ART eligibility was associated with a reduced incidence of HIV-associated KS among adults initiating HIV care in Jos, Nigeria. The reduction was likely driven by earlier enrollment for HIV care and ART initiation.